Penerapan Bimbingan Konseling dalam Pembelajaran Pendidikan Agama Islam di SMP Islam Terpadu Rabbi Radhiyya - Riri Hutami (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims at concrete efforts by PAI teachers in overcoming students' problems, especially in the religious field. This research uses qualitative methods and data collection techniques using observation, interviews and documentation at Rabbi Radhiyya IT Middle School. The results of this research are the application of counseling guidance in Islamic boarding school learning at Rabbi Radhiyya IT Middle School using exemplary methods, habituation, advice and female studies. Apart from that, the factor that supports PAI teachers in dealing with problem students is the existence of spiritual activities, while the inhibiting factor is the limited time that PAI teachers have in carrying out their duties to solve student problems.